Clinical and laboratory features of children with insulin dependent diabetes mellitus of more than two years - Jose R. L. Batubara; Agus Firmansyah; Riza Mansyoer; Bambang Tridjaja; Aman B. Pulungan (Paediatrica Indonesiana, 2001)
The incidence rate of IDDM in our clinic during the period from 1989 to 1998 was 0.028%. There were twentyfour IDDM patients with duration of illness of more than 2 years, with a male to female ratio of 1: 1.5. Most of these patients had no diabetic family history and had good nutritional status. The insulin dosage used by these patients ranged between 0.67 - 0.72 IU/kg/day with a mean of 1.06 IU/kg/day. The average frequency of blood glucose home monitoring was less than ideal. Twenty-two out of the 24 patients were fully controlled metabolically; however, these patients still have polyuria, polydipsia, and polyphagia.